The impact of moderate endurance exercise on cardiac telomeres and cardiovascular remodeling in obese rats - Semeraro, Maria Donatella; Beltrami, Antonio Paolo; Kharrat, Feras; Almer, Gunter; Sedej, Simon; Renner, Wilfried; Gruber, Hans-Jürgen; Curcio, Francesco; Herrmann, Markus (Frontiers in Cardiovascular Medicine, 2023)
Introduction Hypercaloric nutrition and physical inactivity cause obesity, a potential driver of myocardial apoptosis and senescence that may accelerate cardiac aging. Although physical activity reduces mortality, its impact on myocardial aging is insufficiently understood. Here we investigated the effects of a hypercaloric high-fat diet (HFD) and regular exercise training on cardiac cells telomeres and histomorphometric indices of cardiac aging. Methods Ninety-six 4-months old female Sprague-Dawley rats were fed for 10 months normal (ND) or a HFD diet. Half of the animals in each group performed 30 min treadmill-running sessions on 5 consecutive days per week. At study end, cardiomyocyte cross-sectional area (CSA), interstitial collagen content, vascular density, apoptotic and senescent cells, relative telomere length (RTL), and expression of telomerase-reverse transcriptase (Tert) as marker of telomere-related senescence and apoptosis were analyzed. Results Compared to ND, the HFD group developed obesity, higher CSA, lower capillary density and tended to have more apoptotic cardiomyocytes and interstitials cells. Myocardial RTL and the expression of Terf-1 and Terf-2 were comparable in sedentary HFD and ND animals. In the HFD group, regular moderate endurance exercise improved myocardial vascularization, but had no effect on CSA or apoptosis. Notably, the combination of exercise and HFD increased senescence when compared to sedentary ND or HFD, and reduced RTL when compared to exercise ND animals. Exercising HFD animals also showed a trend toward higher Tert expression compared to all other groups. In addition, exercise reduced Terf-1 expression regardless of diet. Conclusion HFD-induced obesity showed no effects on myocardial telomeres and induced only mild morphologic alterations. Summarized, long-term moderate endurance exercise partially reverses HFD-induced effects but may even trigger cardiac remodeling in the context of obesity.